2002
DOI: 10.1167/2.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The multifocal visual evoked potential and cone-isolating stimuli: Implications for L- to M-cone ratios and normalization

Abstract: Multifocal visual evoked potentials (mfVEP) were recorded with a pattern-reversing display that modulated only the long wavelength-sensitive (L) cones or only the middle wavelength-sensitive (M) cones. Outside the central 5.8 degrees (radius), the ratio of the amplitudes of the mfVEP responses to L- and M-cone modulation varied across the six subjects, ranging from 1.1 to 1.7. The responses from the central 1 degrees (radius) showed a substantially lower ratio, ranging from 0.8 to 1.1 (average of 0.9). The var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Our data show that, when the chromatic channel mediates flicker detection, the L-/M-cone sensitivity ratios are around unity for all trichromatic observers and for all adaptation conditions used in the present study. This confirms previous proposals (Hood et al, 2002;Kremers et al, 2000;Pokorny, Smith & Wesner, 1991) that a mechanism is present in the chromatic channel that compensates for individual differences in L-and M-cone densities. From the present data, we can extend the presence of the compensatory mechanism to different adaptation conditions.…”
Section: Adaptation In Trichromatssupporting
confidence: 91%
See 1 more Smart Citation
“…Our data show that, when the chromatic channel mediates flicker detection, the L-/M-cone sensitivity ratios are around unity for all trichromatic observers and for all adaptation conditions used in the present study. This confirms previous proposals (Hood et al, 2002;Kremers et al, 2000;Pokorny, Smith & Wesner, 1991) that a mechanism is present in the chromatic channel that compensates for individual differences in L-and M-cone densities. From the present data, we can extend the presence of the compensatory mechanism to different adaptation conditions.…”
Section: Adaptation In Trichromatssupporting
confidence: 91%
“…These ratios are probably related to the number of L-and M-cones that are stimulated (Brainard et al, 2000;Kremers et al, 2000). However, when the psychophysical sensitivities are mediated by the chromatic channel, the L-/M-cone sensitivity ratio is around unity for all subjects with normal color vision (Hood et al, 2002;Krauskopf, 2000;Kremers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The results of other experiments can also be explained on the basis of this idea. A change in cone weightings in multifocal ERGs and multifocal visual evoked potentials has been described [25][26][27] indicating that the L/M ratio can depend on the stimulus and recording technique. As mentioned in the introduction, we found previously that a change in chromatic adaptation changed the L/M ratio in the ERG measured at 30 Hz and in luminance-mediated psychophysical flicker detection thresholds of L-and M-cone isolating stimuli, 23 from which it can be concluded that the spectral sensitivities of the psychophysical luminance channel and the high-frequency flicker electroretinography are similarly altered by chromatic adaptation and therefore share postreceptoral adaptation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…24 Other observations have shown that a ratio close to unity can also occur in the multifocal ERG and the multifocal visual evoked potential. [25][26][27] It was found that the L/M ratio in psychophysical flicker detection thresholds is approximately unity when the red-green chromatic channel underlies flicker detection. 19,28 -30 Furthermore, the 12-Hz ERGs showed less interindividual variability and were less strongly influenced by chromatic adaptation.…”
mentioning
confidence: 99%
“…For example, one could speculate that unlike the L and M cones in the central retina those in the far periphery express or turnover mRNA unequally. The electroretinogram (ERG) has been an effective tool for investigating cone-derived signals in the retina (Hood et al, 2002; Murray et al, 2004) and has recently been proven to accurately predict relative differences in L:M cone ratio across individual in a direct comparison with results in the central retina from adaptive optics imaging (Hofer et al, 2005). However, the putative cone ratio changes that are suggested by the mRNA results are most dramatic in the far periphery beyond 40° of eccentricity with the percentage of cones approaching 100% L near the ora serrata.…”
Section: Introductionmentioning
confidence: 99%